Effect of evaporative weathering and oil-sediment interaction on the fate and behavior of diluted bitumen in marine environments. Part 2. The water accommodated and particle-laden hydrocarbon species and toxicity of the aqueous phase. (January 2018) - Yang, Zeyu; Hua, Yujuan; Mirnaghi, Fatemeh; Hollebone, Bruce P.; Jackman, Paula; Brown, Carl E.; Yang, Chun; Shah, Keval; Landriault, Mike; Chan, Brian
Abstract: In this study, the water accommodated and particle-laden hydrocarbon species, and the toxicity of the aqueous phase after oil-sediment interactions by varying the weathering states of diluted bitumen (Cold Lake blend (CLB)), oil type from light to heavy, and sediment type. Compared to the original oils, the sediment-laden total petroleum hydrocarbons (TPH) contained fewer hydrocarbons in the carbon range < C 10, comparable contents in C 10 – C 16 range, higher contents in both the C 16 – C 34 and > C 34 range. Sediment-laden oil amounts generally decreased with an increased viscosity and asphaltene content of the test oils, as well as with increased sediment particle size. The presence of sediments significantly decreased the oil accommodated in water due to the formation of oil particulate aggregates (OPA) after mixing and settling. Less water accommodated TPH and polycyclic aromatic hydrocarbons (PAHs) were observed for weathered CLB products. However, oil and sediment types did not clearly affect the water accommodated TPH and PAHs. Light molecular PAHs and their alkylated congeners accounted for most of the water accommodated PAH congeners. A microtoxicity test demonstrated that with or without sediment, and regardless of sediment type, the toxicity of the water phase did not change significantly. Light oil of Alberta sweet mixed blend (ASMB) had the highest toxicity, followed by fresh CLB, and then all other oils, suggesting that ASMB and fresh CLB had relatively higher levels of light toxic components dissolved in the water phase compared with the other tested oils. Graphical abstract: Image 1 Highlights: Sediment-laden TPH contained fewer <C10, but higher C16–C34 and >C34 range hydrocarbons. Increased oil viscosity, asphaltene content, and sediment size decreased sediment-laden TPH. Less water accommodated TPH and PAHs were observed for weathered CLB products. Oil and sediment types did not clearly affect the water accommodated TPH and PAHs. Toxicity of the water phase did not vary with sediment type, but vary with oil type.